Pengaruh Beban Pajak Kini, Beban Pajak Tangguhan dan Aset Pajak Tangguhan terhadap Manajemen Laba - Fadhila Septianingrum; Damayanti Damayanti; Maryani Maryani (Penerbit Goodwood, 2022)
Purpose : This study aied to determine the influence of current tax expense, defffered tax expense and deffered tax asset on earnings management. Research Methodology : The research uses quantitative research method. This study used secondary data from annual reports of consumer goods companies listed on the Indonesia Stock Exchange for the period 2016-2019 and the total was 15 companies. The data analyzed using multiple linear regression model with help of software SPSS version 22,0. Result : The result of this study are current tax expense has negatif effect toward earnings manageent, deffered tax expense has positif effect towards earnings management, deffered tax asset does not have effect toward earnings management, current tax expense, deffered tax expense and defferd tax asset simultaneously have positif effect towards earnings management. Limitation : This reseach’s limitations are the short research period and only use consumer goods sector in manufacturing companies as a sample. Contribution : The result obtained can be used for investors consideration when making investment decisions and can be used as references for further research.